Effectiveness and safety of tocilizumab in refractory noninfectious uveitis: a systematic review and meta-analysis - Kang, Huanmin; Wu, Xue; Xu, Hanyue; Huang, Yufan; Zhang, Ming (Frontiers in Pharmacology, 2025)
PurposeThe aim of this study was to comprehensively evaluate the efficacy and safety of tocilizumab in patients with refractory noninfectious uveitis (NIU) through a systematic review and meta-analysis.MethodsA comprehensive literature search was conducted across PubMed, Embase, Web of Science, Cochrane Library, and ClinicalTrials.gov from inception to 13 July 2025. Eligible studies included case series and cohort studies evaluating clinical outcomes of tocilizumab in NIU. Study quality was assessed using the Joanna Briggs Institute Case Series Checklist and Newcastle–Ottawa Scale. A single-arm meta-analysis was performed using a random-effects model.ResultsThirteen studies involving 374 patients were included. The pooled rate of sustained inactive uveitis was 57.08% (95% CI: 46.94%–66.96%), and the overall inflammation remission rate at the final follow-up was 75.23% (95% CI: 64.04%–85.09%). Macular edema resolved in 93.22% of patients (95% CI: 86.76%–98.01%), with a mean reduction in a central macular thickness of 143.57 µm. Mean visual acuity improved by −0.29 logarithm of the minimum angle of resolution (logMAR) (95% CI: −0.55 to −0.04). The pooled glucocorticoid discontinuation rate was 40.25% (95% CI: 13.43%–70.27%). During the follow-up period, the pooled incidence of adverse events and serious adverse events was 13.05% (95% CI: 8.88%–17.78%) and 4.41% (95% CI: 1.08%–9.16%), respectively. Subgroup analysis suggested greater efficacy among patients treated for ≥9 months.ConclusionTocilizumab provides meaningful clinical benefit with acceptable safety in refractory NIU related to autoimmune and inflammatory diseases, particularly in patients with macular edema. These results support the use of tocilizumab as a viable second-line therapeutic option following the failure of conventional immunosuppressants and antitumor necrosis factor alpha agents.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251069626, identifier CRD420251069626.